“Formulation and evaluation of microemulsion based gel of Calendula officinalis extract and its anti-microbial activity” - MD HAMID ANSARI; ASHISH JAIN; MAHADEV KANERE; AKHLESH KUMAR SINGHAI (International Journal of Multidisciplinary Research and Studies, 2024)
The present study focuses on the formulation and evaluation of a micro emulsion-based gel containing Calendula officinalis extract, targeting its potential as an antimicrobial agent. Micro emulsions offer a unique advantage in enhancing the solubility and bioavailability of hydrophobic plant extracts, thereby improving their therapeutic efficacy. Qualitative phytochemical screening of Calendula officinalis showed the presence of active metabolites such as Alkaloids, flavonoids, glycosides, carbohydrates, saponin, tannins and phenols. The micro emulsion was prepared using oil, surfactant, and co-surfactant systems, followed by its incorporation into a gel matrix. The formulated micro emulsion-based gel was characterized for physicochemical properties such as pH, viscosity, spread ability, and stability. The viscosity of microemugel is found to be 6891 ±0.37 cps. The pH of microemugel is 6.5 and spread ability is 11.18, indicating that microemugel has high release and permeability. The microemugel's creation and shape were verified using SEM images. Furthermore, the antimicrobial efficacy of the gel was assessed against common pathogenic microorganisms including Escherichia coli through in vitro studies. The results demonstrated significant antimicrobial activity, suggesting the potential application of this formulation in topical antimicrobial therapy. The study concludes that the micro emulsion-based gel of Calendula officinalis extract exhibits promising characteristics for the development of effective antimicrobial treatments.